Press Censorship in Jacobean England - Clegg, Cyndia Susan (Cambridge University Press, 2001)
This book examines the ways in which books were produced, read, and received during the reign of King James I. Cyndia Clegg contends that although the principal mechanisms for controlling the press altered little between 1558 and 1603, the actual practice of censorship under James I varied significantly from Elizabethan practice. The book combines historical analysis of documents with the reading of censored texts and will be an invaluable resource for scholars as well as historians.